ArcGIS for Assessment and Display of the Probability of Forest Fire Danger; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Yankovich E. P. Elena Petrovna (Information & Communication Technology, 2014)
Title screen